2019
DOI: 10.14716/ijtech.v10i4.2574
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Use of Innovative Bamboo Products for the Construction of Residential Buildings in Nigeria

Abstract: The high cost and environmental and health hazards attributed to conventional building materials, coupled with the adverse effect of massive exploitation of forest resources for construction purposes, have necessitated the search for alternative construction materials that are eco-friendly, sustainable, economical and socially acceptable. This study aims to explore the acceptability and use of innovative bamboo products for residential building construction in Nigeria. One hundred and fifty-two survey question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Ameh, et al [44] Acceptability and use of innovative bamboo products for the construction of residential buildings in Nigeria.…”
Section: Ezema Andmentioning
confidence: 99%
“…Ameh, et al [44] Acceptability and use of innovative bamboo products for the construction of residential buildings in Nigeria.…”
Section: Ezema Andmentioning
confidence: 99%
“…formwork and scaffolding) while noting the average level of awareness and experience on the application of bamboo as structural members, particularly for traditional roofs and wall construction. In a study of professionals' perception of acceptability and use of innovative bamboo products for residential building construction, Ameh et al (2019) further show likely disposition to use bamboo plywood, bamboo fiber board, laminated bamboo for general use as a substitute for wood, as well as bamboo board for wall partitions, and bamboo strips for both ceiling and flooring. Sharma et al (2017) found that laminated bamboo possesses structural properties comparable to timber and timber-based products.…”
Section: Introductionmentioning
confidence: 99%
“…Predominantly used conventional building materials include concrete, steel, and wood. Ameh et al (2019), listed the shortcomings of conventional materials such as concrete and steel to include: high cost, a substantial amount of energy required for their production and transportation, huge foreign exchange required for importation of constituent materials and heavy machinery for their production, and artificial ventilation necessitated by poor indoor thermal comfort in buildings made from modern construction materials. Wood and wood products on the other hand are eco-friendly conventional materials; however, the demand for wood as a forest resource continues to increase in proportion to the human population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This product has mechanical properties comparable to or superior to structural wood and plywood. The use of processed bamboo products in construction is still a developing field (Ameh et al, 2019; Comparison of Physical and Mechanical Properties of Bamboo Laminates With and Without 11 Natural Fiber Reinforcement Mochamad Chanan, Galit Gatut Prakosa, Aditya Galih Kurniawan Khandkar-Siddikur et al, 2012;Akwada & Akinlabi, 2015). This study will reveal differences in physical and mechanical properties between combination treatments (fiber bonding and non-fiber bonding) and the relationship between variables including moisture content, density, modulus of elasticity (modulus of elasticity, MOE, Eapp), and flexural strength (modulus of rupture, MOR, SR).…”
Section: Introductionmentioning
confidence: 99%